Testes de conservação natural pós-colheita, além dos 300 dias, de frutos de alguns cultivares de tomateiro (Lycopersicon esculentum Mill) e híbridos destes com "Alcobaça" - Rocha Leal , Nilton; Tabim, Maria Helena (Revista Ceres, 2025)
This experiment was conducted from 1972 to 1973 at the Federal University of Viçosa to study natural post - harvest conservation of fruits of various tomato varieties as well as reciprocal hybrids of these varieties with the commercial variety ’Alcobaça’. Two experiments were performed, one of 350 days and one of 340 days. All of the hybrid fruits exhibited superior post harvest performance than the parents, with the exception of ’Alcobaça’. Differences among the fruit types in weight loss during the storage period were not significant.